Investigating the participation of children on the autism spectrum across home, school, and community: A longitudinal study. (20th May 2019) - Simpson, Kate; Adams, Dawn; Bruck, Susan; Keen, Deb
Abstract: Background: The World Health Organization recognizes that meaningful participation in one's community empowers individuals. Children and adolescents on the autism spectrum consistently report lower participation than their typical peers in activities, and this appears to continue into adulthood. The aim of this study was to investigate the participation of children on the autism spectrum over a 3‐year period across home, school, and community. Method: Caregivers of 84 participants aged 9–10 years at Year 1 completed the Participation and Environment Measure for Children and Youth (PEM‐CY) at three annual data collection points. The PEM‐CY is a 25‐question measure of the child's level of involvement in home, school, and community activities. Distribution frequencies were calculated for each time point. Results: Although participation in the majority of items across home, school, and community remained stable, the longitudinal data suggest that children change the types of socializing activities across time. Over the 3 years, there was a decline in physical activity (both organized and unstructured) and in participation in school activities. Conclusion: This decline in participation as children move into adolescence is concerning. Further, reduced participation at this phase of development may potentially limit future participation opportunities throughout adolescence and into adulthood. Further exploration of the participation trajectories of children on the autism spectrum is needed.